Qatar's sports strategy: a case of sports diplomacy or sportswashing? - Søyland, Håvard Stamnes (2021)
In December 2010 Qatar won the rights to host the 2022 FIFA World Cup. In the following years Qatar have gained significant influence within global sports. The small desert state has hosted several international sporting events during the last decade and increased its global presence by investing in international sports though sponsorship deals, acquisition of football clubs, acquiring broadcasting rights and the creation of state-of-the-art sporting facilities. This thesis looks at how Qatar utilises sports diplomacy to gain attraction and soft power globally, drawing on document analyses of key Qatari governmental documents. Qatar’s engagement in global sports follows an international development, where autocratic resource rich regimes have become major actors within global sports in the recent years. While Qatar’s sports diplomacy has been very ambitious, the newfound global attention has led to an increased scrutiny regarding Qatar’s internal policies. This have resulted in massive and consistent criticism regarding corruption allegations and several reports about labour abuses facing the migrant workers in the country. This thesis argues that Qatar’s sports diplomacy needs to be looked at in a critical light. The concept of sportswashing is a fitting description of how Qatar’s sports strategy deliberately seeks to alter its global reputation by being associated with the global appeal of sports while unsuccessfully divert the attention away from the internal politics in the country.